(untitled) (Edad Media. Revista de Historia, 2023)
This study sets out to specify the identity and characteristics of the opposing sides in the Navarrese civil war at the end of the Middle Ages (1450-1507). To that end, an analysis of the lexicon used in the texts of the time to describe the factions and their members is carried out. In particular, this article draws from documentation from opposing sides, such as testimonies of grievances, capitulations and the granting of privileges. The data obtained enables us to understand the evolution of the conflict, initially a confrontation of dynastic allegiances followed by the consolidation of an actual war between noble factions. The data obtained also help us to understand the Agramontese and Beaumontese as complex groups, led by nobles but consisting of people of different social status, their common denominator being the exercise of violence and their active participation in the war.